Numerical solution for an epicycloid crack - Nik Long, Nik Mohd Asri; Koo, Lee Feng; Wong, Tze Jin; Eshkuvatov, Zainidin K. (Hindawi Publishing Corporation, 2014)
A flat crack, , is lying in a three-dimensional homogenous isotropic elastic solid subjected to shear loading. A mathematical formulation is developed based on the mixed boundary values for such that the problem of finding the resulting force can be written in the form of hypersingular integral equation. Employing conformal mapping, the integral equation is transformed to a similar equation over a circular region, . By making a suitable representation of hypersingular integral equation, the problem is reduced to solve a system of linear equations. Numerical solution for the shear stress intensity factors, maximum stress intensity, and strain energy release rate is obtained. Our results give an excellent agreement to the existing asymptotic solutions.